2020
DOI: 10.1098/rsta.2019.0334
|View full text |Cite
|
Sign up to set email alerts
|

Predicting left ventricular contractile function via Gaussian process emulation in aortic-banded rats

Abstract: Cardiac contraction is the result of integrated cellular, tissue and organ function. Biophysical in silico cardiac models offer a systematic approach for studying these multi-scale interactions. The computational cost of such models is high, due to their multi-parametric and nonlinear nature. This has so far made it difficult to perform model fitting and prevented global sensitivity analysis (GSA) studies. We propose a machine learning approach based on Gaussian process emulation of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…And thirdly, our models are coupled to fixed Windkessel models as boundary conditions, as opposed to a closed loop cardiovascular system, where changes in cardiac stroke volume, in either ventricle, can feedback and result in alterations in the preload and afterload that can, in turn, change the cardiac cycle timings. However, previous studies [ 44 ] found that boundary conditions did not have a significant influence on cardiac output, albeit in a rat model. Our results from the local sensitivity analysis agree with [ 44 ], showing that the results are not overly sensitive to the stiffness of the boundary conditions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…And thirdly, our models are coupled to fixed Windkessel models as boundary conditions, as opposed to a closed loop cardiovascular system, where changes in cardiac stroke volume, in either ventricle, can feedback and result in alterations in the preload and afterload that can, in turn, change the cardiac cycle timings. However, previous studies [ 44 ] found that boundary conditions did not have a significant influence on cardiac output, albeit in a rat model. Our results from the local sensitivity analysis agree with [ 44 ], showing that the results are not overly sensitive to the stiffness of the boundary conditions.…”
Section: Discussionmentioning
confidence: 82%
“…We performed a GPE-based GSA as in [ 44 ]. Briefly, we trained one GPE per phenotype defined in Table 1 , with the exception of phenotypes whose range of variability was below a threshold, determined below, across the cohort.…”
Section: Methodsmentioning
confidence: 99%
“…In order to perform a systematic investigation on the importance of each model parameter, we fitted a Gaussian process emulator [12,13] to our model, enabling us to perform a GSA. GSA's aims to quantify the relative importance of input variables in determining the value of an assigned output variable [14], which in our model is represented as activation times, collected on the top right corner of the tissue slab.…”
Section: Gaussian Processes Emulator and Global Sensitivity Analysismentioning
confidence: 99%
“…Di Achille et al [ 32 ] inferred the unloading LV geometry used Gaussian process and further statistically learned the infarct shape and size on LV performance in patients extracted from a public database [ 33 ]. More recently, Longobardi et al [ 34 ] predicted left ventricular contractile function via Gaussian process emulation in aortic-banded rats, the Bayesian history matching was applied to constrain the initial parameter sets in order to exclude those points which generate non-physiological biomechanical models. They further performed a Sobol sensitivity analysis using the trained emulator.…”
Section: Introductionmentioning
confidence: 99%